2019
DOI: 10.3390/medicina55090581
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Periodontitis and Its Association with Reduced Pulmonary Function: Results from the Korean National Health and Nutrition Examination Survey

Abstract: Background and Objectives: The current study was performed to evaluate the prevalence of periodontitis and to examine the association between reduced pulmonary function and periodontitis using Sixth Korea National Health and Nutrition Examination Survey (KNHANES) in 2014. Materials and Methods: A cross-sectional evaluation was conducted to estimate the prevalence of periodontitis and to examine the association between periodontitis and reduced pulmonary function while adjusting for sociodemographic characteris… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
18
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 41 publications
(46 reference statements)
0
18
0
Order By: Relevance
“…Jung et al 24 stated that the periodontal status was not significantly associated with COPD. A crosssectional evaluation conducted by Lee et al 23 indicated that the risk of periodontitis was not significantly associated with lung function. Bergstrom et al 40 found that COPD was not associated with the risk of impaired dental health.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Jung et al 24 stated that the periodontal status was not significantly associated with COPD. A crosssectional evaluation conducted by Lee et al 23 indicated that the risk of periodontitis was not significantly associated with lung function. Bergstrom et al 40 found that COPD was not associated with the risk of impaired dental health.…”
Section: Discussionmentioning
confidence: 99%
“…[16][17][18][19][20][21][22] Whereas some other studies have indicated no significant relationship between them. [23][24][25][26] The results for the association between periodontitis and lung function are not entirely consistent. Therefore, based on the data from the National Health and Nutrition Examination Survey (NHANES) 2009 to 2012, we intended to investigate the association between periodontitis and lung function.…”
Section: Introductionmentioning
confidence: 88%
“…The lack of association may root in using CPIs to classify periodontal status. Previous studies have reported that CPIs may not provide a whole picture of an individual’s periodontal status due to the use of index teeth as in our study where only the ten index teeth were examined at the most [ 27 29 ]. Moreover, because CPIs do not measure clinical attachment loss, they may underestimate the prevalence of PD [ 27 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have reported that CPIs may not provide a whole picture of an individual’s periodontal status due to the use of index teeth as in our study where only the ten index teeth were examined at the most [ 27 29 ]. Moreover, because CPIs do not measure clinical attachment loss, they may underestimate the prevalence of PD [ 27 29 ]. Also, the high prevalence of PD across all levels of frailty in our study (more than 40%, in both frailty models) may have affected the results from our analyses.…”
Section: Discussionmentioning
confidence: 99%
“…A heavier burden of periodontitis was found in US adults aged 65 years old and above, with 64.1% for mild/moderate periodontitis ( Eke et al., 2016 ). Korea NHANES in 2014 revealed that 41.1% of survey population aged from 40 to 79 years old suffered from periodontitis ( Lee and Lee, 2019 ). Additionally, cross-sectional studies in Norway presented that nearly 50% of population had periodontitis, with 9.1% in severe form or 20.1% in periodontitis stage III/IV ( Holde et al., 2017 ; Bongo et al., 2020 ).…”
Section: Introductionmentioning
confidence: 99%